Reproduction Under Stress: Acute Effect of Low Salinities and Heat Waves on Reproductive Cycle of Four Ecologically and Commercially Important Bivalves - Vázquez, Elsa; Woodin, Sarah A.; Wethey, David S.; Peteiro, Laura G.; Olabarria, Celia (Frontiers in Marine Science, 2021)
Given the ecological and socioeconomic importance of estuaries, the impacts of climate change on their structure and functioning is a major focus of concern, even more when the affected species support important fisheries as the venerid clams Ruditapes decussatus, R. philippinarum, Venerupis corrugata, and the cockle Cerastoderma edule in Europe whose reproductive performance, in the context of climate stressors, has not yet been investigated. Thus, our objective was to experimentally evaluate the potential effect of low salinity and atmospheric heatwave stresses on their reproductive cycle. To test it, bivalves were exposed during six days to four different salinity ramps (5-20, 10-25, 15-30, 30-30) during simulated tidal cycles over three different periods of the year (autumn, winter and spring); also, in summer, they were exposed to atmospheric heatwaves at low tide (20, 27, 32, 37°C) during four consecutive days. Histological slides were analyzed to determine their gametogenetic stage and a gonadal index was calculated. Both low salinity and heatwave stresses compromised reproduction but the response was species-specific dependent and varied with the time of the year, therefore with the gametogenic cycle. In December, during sexual resting and the beginning of gametogenesis, a delay in the gametogenesis was recorded in the four species at lower salinities. In March and May, at the peak of the reproductive period, the response was different; abnormal oocytes in R. decussatus and resorption of gametes with hemocytic infiltration in R. philippinarum and V. corrugata were observed. Sediment temperatures higher than 32ºC provoked gonadal resorption and severe hemocytic invasion in V. corrugata, R. decussatus and C. edule but no effect in R. philippinarum. These responses were related to the allocation of energy from reproduction towards defense and repair mechanisms to ensure survival. Contrastingly, low salinities triggered massive spawning in C. edule that could lead to a mismatch between the presence of larvae and phytoplankton, causing potentially starvation and thus reducing recruitment success. For short-lived species as these bivalves if low salinity episodes in winter and spring are followed by a heatwave in summer, reproduction would be compromised, and the impact magnified if this situation happens during consecutive years